Tanggung Jawab Hukum Dalam Pengadilan Pengaduan Yang Menyebabkan Pencemaran Nama Baik - Moh Khoiron; Syarig .; Moh. Taufik (JOURNAL OF SHARIA ECONOMICS, 2022)
Defamation through unfounded complaints in the judicial process is a serious problem that is often faced in the Indonesian legal system. This article aims to discuss legal responsibility in cases of complaints that result in defamation, as well as analyzing how Indonesian law handles complaints that are slanderous or defamatory. The research method used in this article is a qualitative approach, with data collection through literature studies and interviews with legal practitioners. The research results show that even though there are provisions in Indonesian law regarding defamation, many cases are not resolved fairly, especially those related to complaints that cannot be justified. The recommendations put forward include the need to improve regulations related to protecting individuals from slander and defamation in the judicial process, as well as increasing public awareness of the importance of respecting other people's rights to privacy and reputation.